Asiaticoside and Madecassoside from Centella asiatica Demethylate the Nrf2 Promoter and Enhance Neuroprotection In Vitro - Akmal Hasan; Wisnu Wardhana Putra (HM Publisher, 2025)
Centella asiatica (L.) Urban (Apiaceae), known as pegagan in Indonesian Jamu and Brahmi in Ayurveda, contains triterpene saponins with reported neuroprotective properties, yet the epigenetic mechanisms remain poorly understood. This study investigated whether a triterpene-enriched fraction (TEF) standardized to asiaticoside (28.4%) and madecassoside (22.7%) modulates Nrf2/HO-1 pathway activation through promoter demethylation and histone acetylation in oxidatively stressed SH-SY5Y neuroblastoma cells. Cells were pre-treated with TEF (25, 50, 100 μg/mL) for 24 hours before H2O2 (200 μM) challenge. TEF at 100 μg/mL restored cell viability to 82.4 ± 4.3% versus 47.8 ± 4.1% in H2O2-only cells (p < 0.001, Cohen’s d = 8.22), reduced ROS to 1.52 ± 0.15-fold (p < 0.001), and upregulated Nrf2 mRNA 2.83 ± 0.21-fold and HO-1 protein 3.14 ± 0.24-fold. Bisulfite sequencing revealed dose-dependent Nrf2 promoter demethylation from 67.8 ± 4.2% to 31.2 ± 2.6% (p < 0.001), paralleled by DNMT1 suppression (2.74 to 1.12-fold) and H3K27ac enrichment (0.34 to 1.43-fold) at the Nrf2 locus. A strong inverse correlation between methylation and Nrf2 expression (r = −0.912) and closely aligned IC50 values for ROS suppression (62.4 μg/mL) and demethylation (58.7 μg/mL) support a coordinated epigenetic-transcriptional mechanism. These findings provide the first evidence that Centella asiatica triterpenes activate neuroprotective pathways through dual epigenetic remodeling, offering a molecular rationale for the traditional cognitive-enhancing applications of this ethnopharmacologically significant herb.